Clinical and Counseling Experiences of Early Adopters of Whole Exome Sequencing. Issue 2 (19th August 2015) - Arora, Shubhangi; Haverfield, Eden; Richard, Gabriele; Haga, Susanne B.; Mills, Rachel
Abstract: Currently, there are limited data regarding the practice of genetic counseling for whole exome sequencing (WES). Improved understanding of how genetic counselors and other providers are educating, counseling, and communicating results may identify practice trends, and patient or provider needs. Between April 2013 and December 2014, we surveyed providers who ordered WES testing from GeneDx, a CLIA‐certified laboratory. Forty‐nine respondents completed the survey; 41 % of participants reported board certification in genetic counseling. Pre‐test and post‐test counseling was completed in all but one case each. Pre‐test counseling lasted less than 1 h for 53 % of cases and 1 to 2 h for 43 %. Topics discussed with all patients included consent for testing, and incidental findings; other topics were variable. In contrast to pre‐test counseling, 59 % reported post‐test counseling lasting 1 to 2 h and 33 % less than an hour; post‐testing counseling was significantly longer in cases with a definitive diagnosis than those without ( p  = 0.0129). The survey findings indicate some variability regarding the amount of time spent on counseling and the topics discussed during pre‐test counseling. Additional exploration, patient and provider educational resources, and potentially more specific guidelines regarding counseling for WES may be warranted.